The time series behaviour of corporate earnings in Singapore - Chew, Chee Yuen (2015)
Existing evidence indicates that the time-series behavior of corporate annual earnings is well approximated by a random walk, or some similar processes. However, no evidence on this issue has been collected in Singapore. This report presents the results of an investigation into the time-series behavior of the annual earnings of a sample of relatively large corporations listed on the Stock Exchange of Singapore. The conclusions, that successive changes in such earnings are well approximated by a random walk, is consistent with existing evidence.